Study of Young Adults' Preferences in Passenger Rail Transport Services as a Basis for Marketing Activities - Grazyna ROSA; Izabela OSTROWSKA; Agnieszka TOMASZEWICZ (Communications of International Proceedings, 2020)
Since the 1990s, the macro environment of passenger transport companies has changed radically. As a consequence of changing conditions, marketing is being atomised and the demand for new marketing instruments is rapidly increasing. In societies of abundance, consumers are better educated and more demanding, thus a need arises for new marketing activities and adapting products to the requirements of the target market, taking into account the individual needs of buyers. This article focuses on the literature concerning young people, especially the group of young adults (18-29 years old) who often travel and are considered an important target group for railway companies due to continuing education outside their place of residence, work or sightseeing. The research investigates passenger rail transport in regions and agglomerations in Poland. In order to achieve the research objective, the method of critical analysis of available results of secondary research and a questionnaire in primary research were used. Modern marketing in passenger rail transport services should therefore target areas where particular factors are related to travel times, service prices, customer service processes and availability of new technologies.
Keywords: Passenger Rail Transport; Customer Preferences; Marketing.